(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The purpose of our investigation was to determine the most informative physiological characteristics to monitor training effect in highly qualified road cyclists.Fourteen Latvian Olympic Team road cyclists with training experience from seven to nine years participated in theinvestigation voluntarily (their average age was 19.3 ± 1.1 years, height — 183.6 ± 5.4 cm, body mass — 73.4 ± 3.8 kg). The aerobic performance tests were carried out in the Latvian Olympic Team Laboratory at the initial and middle phase of their preparation period of training. The initial load of 27 W was increased every two minutes step by step by 12 W. The cardiopulmonary diagnostic equipment was used to register the electrocardiograms and respiratory characteristics. The lactic acid concentration in the capillary blood was tested. The maximal oxygen uptake (4.62 ± 0.40 l / min and 63.2 ± 4.8 ml / kg·min) and power output (376 ± 36 W and 5.13 ± 0.44 W / kg) in the cyclists were significantly lower in comparison with the data received by other authors. At the initial or middle phase of the preparation period of training these characteristics did not reach their maximal values. The oxygen uptake (3.85 ± 0.30 l / min and 52.6 ± 3.7 ml / kg·min) and power output (296 ± 28 R and 4.04 ± 0.33 W / kg) at the anaerobic threshold intensity load were in a good agreement with the data of other investigators. These characteristics depend on the central and peripheral mechanisms of aerobic capacity in the cyclists, and are useful in the estimation and monitoring of the endurance performance. The data reported by different authors of aerobic threshold physiological characteristics in highly qualified cyclists were contradicting, which can be explained by different test protocols and differences in the rate of lactate accumulation in the capillary blood, especially in the initial phase of the test. Our investigations showed that the oxygen uptake was 2.57 ± 0.35 l / min and 35.0 ± 4.7 ml / kg·min, and power output was 182 ± 36 W and 2.48 ± 0.47 W / kg. The mechanical efficiency (21.9 ± 1.2%) and economy of cycling movements (4.602 ± 0.268 kJ / l) in the cyclists reached their maximal values at the anaerobic threshold, which is the intensity of load specific to road cycling. It proves high homogeneity of the mechanical efficiency and economy of movements among the cyclists, and lack of the significant correlation between these characteristics and the power output on the bicycle ergometer (r = 0.19 and 0.20, respectively; p > 0.05). Keywords: cycling, aerobic capacity, work mechanical efficiency, aerobic and anaerobic thresholds.